2015
DOI: 10.1016/j.bmc.2015.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Singlet oxygen oxidation products of biliverdin IXα dimethyl ester

Abstract: Biliverdin IXα is a naturally occurring linear tetrapyrrolic product of the enzymatic oxidative ring cleavage of heme. Evidence is mounting that biliverdin possesses antioxidant properties in mammals but its mode of action is unclear. We present the single crystal X-ray structure analysis of two regioisomeric biladien-1,19-diones-ab that are derived from biliverdin IXα dimethyl ester by addition of two vicinal trans-methoxy groups to the 4,5- or 15,16-double bonds, respectively. The compounds were likely forme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…Biliverdin possesses antioxidant properties in mammals. Structural evidence for a possible reaction mechanism by which biliverdin can act as an antioxidant is given in Dorazio et al 44 Table 2 compares the Raman frequencies of our sample with Raman frequencies published for biliverdin in Hu et al 45 These authors analyzed five biliverdin compounds using FT-Raman and FT-IR and gave the wavenumbers and corresponding assignments of their vibrational modes obtained. With Raman, they used an excitation laser at 1064 nm that is relatively far from our own excitation line at 514.5 nm, but different excitation frequencies can produce a great variation of the resulting Raman spectra.…”
Section: Raman Vibrations Of Biliverdin and Similar Structuresmentioning
confidence: 88%
“…Biliverdin possesses antioxidant properties in mammals. Structural evidence for a possible reaction mechanism by which biliverdin can act as an antioxidant is given in Dorazio et al 44 Table 2 compares the Raman frequencies of our sample with Raman frequencies published for biliverdin in Hu et al 45 These authors analyzed five biliverdin compounds using FT-Raman and FT-IR and gave the wavenumbers and corresponding assignments of their vibrational modes obtained. With Raman, they used an excitation laser at 1064 nm that is relatively far from our own excitation line at 514.5 nm, but different excitation frequencies can produce a great variation of the resulting Raman spectra.…”
Section: Raman Vibrations Of Biliverdin and Similar Structuresmentioning
confidence: 88%
“…5). Whether the first biliverdin oxidation step actually takes place at the bond indicated or at the adjacent www.nature.com/scientificreports/ double bond, followed by the loss of the meso-carbon, cannot be determined, but direct and circumstantial evidence exist that at least singlet oxygen reacts specifically with the double bond 33,38 . Bilirubin 4 H is a well-studied catabolite of biliverdin 39 , generated through a reductive enzymatic process 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Though the exact mechanism is not known, previous reports reveal that biliverdin is a potential antioxidant in the biliverdin/ bilirubin cycle in the presence of biliverdin reductase and helps cytoprotection (53)(54)(55)(56). However, Dorazio et al (57) have recently shown that biliverdin itself may have antioxidant properties, which might be an added advantage for walleyes for survival in their native environment. Schaefer et al (3) have shown that the number and level of sandercyanin in the mucus of blue walleye increases seasonally, in the summer, as solar UV input increases.…”
Section: Crystal Structures Of Apo-and Holo-sandercyanin Reveal Molecmentioning
confidence: 94%